Hong Kong, China : Growth, Structural Change, and Economic Stability During the Transition - Mihaljek, Dubravko; Dodsworth, John. (Washington, D.C. : International Monetary Fund, 1997)
This paper provides a detailed account of Hong Kong on the eve of its reintegration into China as a special administrative region. It analyzes recent economic development and provides a clear overview of Hong Kong's economic, financial, institutional, and political circumstances, as well a brief look at its history over the last hundred years. It suggests the changes the economy will undergo in the transition process and what it can expect in the future.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet